Identifikasi Kebutuhan Asuhan Women Center Care Berbasis Aplikasi Pada Calon Pengantin Perempuan Yang Merencanakan Kehamilan - Eka Vicky Yulivantina; Yudha Christianto Firmansyah; Bambang Budi Raharjo (Universitas Sumatera Barat, 2025)
Maternal Mortality Rate (MMR) remains a significant public health concern in Indonesia, with most maternal deaths caused by pregnancy-related complications that are largely preventable through continuous midwifery care. The women center care approach places women at the center of care and represents an essential strategy for pregnancy planning beginning in the preconception period. Although digital applications have been implemented in premarital and preconception health services, their utilization has not yet fully reflected the principles of women-centered care. This study aimed to identify the need for application-based women-centered care among prospective brides planning pregnancy. A qualitative study with a phenomenological approach was conducted. Participants were selected purposively and included primary health care center heads, coordinating midwives responsible for maternal and child health services, and prospective brides who utilized premarital health services. Data were collected through in-depth interviews and analyzed using the PIECES framework (Performance, Information, Economy, Control and Security, Efficiency, and Services). The findings indicated that the currently used applications—ELSIMIL, Puscatin, and ILP—primarily focus on pregnancy eligibility screening and stunting prevention and do not comprehensively address broader preconception care needs. Limitations were identified in information provision, efficiency, continuity of care, follow-up mechanisms, and data control and security. Furthermore, no application currently supports continuous care and women’s empowerment in accordance with women-centered care principles. This study concludes that the development of an integrated, sustainable, and women-centered preconception application is critically needed to support healthy and safe pregnancy planning.